1995
DOI: 10.1159/000172313
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of Hepatectomy for Hepatocellular Carcinoma

Abstract: Intraoperative blood loss is well associated with the immediate outcome after hepatic resection particularly in cirrhotic patients. Temporary occlusion of the hepatic inflow (Pringle’s maneuver) effectively suppresses the blood loss and postoperative mortality. This technique is safe for 60-70 min in noncirrhotic and for 30 min in cirrhotic patients. Total vascular exclusion of the liver is rarely indicated but useful in resecting tumors adjacent to or growing in the main hepatic veins or inferior vena cava. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…However, TACE can also achieve good results, although it is not thought of as curative. Nagasue et al 9 also concluded that repeat hepatectomy may be useful for recurrent HCC, and they suggested that repeat hepatectomy was indicated principally for patients with a solitary tumor and Child grade A liver disease. These groups of authors [7][8][9] considered that repeat hepatic resection for recurrent HCC was beneficial, but they did not analyze recurrent HCC by distinguishing MC from IM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TACE can also achieve good results, although it is not thought of as curative. Nagasue et al 9 also concluded that repeat hepatectomy may be useful for recurrent HCC, and they suggested that repeat hepatectomy was indicated principally for patients with a solitary tumor and Child grade A liver disease. These groups of authors [7][8][9] considered that repeat hepatic resection for recurrent HCC was beneficial, but they did not analyze recurrent HCC by distinguishing MC from IM.…”
Section: Discussionmentioning
confidence: 99%
“…Nagasue et al 9 also concluded that repeat hepatectomy may be useful for recurrent HCC, and they suggested that repeat hepatectomy was indicated principally for patients with a solitary tumor and Child grade A liver disease. These groups of authors [7][8][9] considered that repeat hepatic resection for recurrent HCC was beneficial, but they did not analyze recurrent HCC by distinguishing MC from IM. Here, we have reported the survival rates of 29 patients (who underwent a total of 31 second and third operations, including hepatectomy and MTC, for recurrent HCCs) according to the mode of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although recurrence following resection of HCC is associated with a poor outcome in most cases, there is growing evidence that some patients will benefit from more aggressive approaches, especially if the recurrence is limited to the liver [77][78][79]. Multimodality therapy including TACE, percutaneous ablative therapy, and re-resection could result in prolonged survival with an overall 5-year survival rate of 20% [30,71,73,80,81].…”
Section: Recurrence Following Resection Of Hccmentioning
confidence: 99%
“…Several studies have reported on repeat hepatectomy for intrahepatic recurrence. [2][3][4][5][6][7] According to the study of Poon et al, 7 the overall 1-year, 3-year, and 5-year survival rates from the time of recurrence were 65.5%, 34.9%, and 19.7%, respectively, and those from the time of initial hepatectomy were 78.4%, 47.2%, and 30.9%, respectively. They examined survival rates in relation to therapeutic modalities, and showed that the re-resection group had the best survival, followed by the transarterial chemoembolization group.…”
Section: Repeat Hepatectomy For Intrahepatic Recurrencementioning
confidence: 99%